Pemeliharaan Pompa Hydram Untuk kegiatan Holtikultura Di Desa Cikupa Karangnunggal Tasikmalaya - Mochamad Irlan Malik; Anes Inda Rabbika; Muhammad Hanhan Nugraha; Yanti Yanti; Andy Permana Rusdja; Ahmad Bustomi (KREATIF: Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2025)
The hydram pump is a simple technology that utilizes the kinetic energy of water to pump water to a higher elevation without requiring external energy sources such as electricity or fuel. This technology is highly suitable for rural areas, especially in regions with limited access to electricity and other resources. Cikupa Village, Karangnunggal District, is one of the areas that utilizes the hydram pump to support water needs for horticultural activities. The Community Service Program (PKM) aims to ensure that the hydram pump continues to function optimally through a series of maintenance activities. The methods employed in this program include thorough inspections of the pump components, identification of damages, replacement of non-functional components, and post-repair operational testing. In addition, the PKM team also provides training to the local community on how to operate the pump, basic maintenance techniques, and the importance of regular maintenance to ensure the long-term sustainability of this technology. Outreach efforts are carried out to raise awareness among the community about the benefits of the hydram pump and its impact on their well-being. The results of the program show that the hydram pump was successfully repaired, restoring its ability to produce sufficient water flow to meet the community's needs. Furthermore, the community now has the ability to perform maintenance independently, ensuring the sustainability of this technology in the future